Depiction of river goddesses Ganga and Yamuna on the doorframe - Temples of India Project Team (Jio Institute, 2024)
The lower section of the doorframe of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple portrays the river goddesses Ganga and Yamuna. In this picture, on the right side, Ganga is represented, identifiable by the broken makara (crocodile-like mythical creature) at the base. The figures next to the river goddesses depict Shiva as a four-armed figure. He holds a khatvanga (staff with a skull) and a sarpa (snake) in his upper hands. His lower right hand, holding an akshmala (rosary), is in the varadahasta (boon-giving gesture). In his lower left hand, he holds a bowl. He wears a jatamukuta (a crown of matted hair) and is adorned with heavy jewellery. At the bottom left, there is a Nandi that is now damaged. The figure beside Shiva depicts female attendants, while the figure at the end represents Kubera, who is portrayed with two arms and a money bag.